On a Botanical Trip to the Source of the River Ganga in Terri Garhwal Himalayas - Gupta, Raj Kumar (Indian Forester, 1960)
The paper presents vegetation of the Bhagirathi Ganga valley as seen by the author during his trip. Climate, gt:ology, soil and biotic factors have been presented in the paper. The main types of vegetation observed are (1) Tropical winter deciduous forests, (2) Pinus roxburghii forests, (3) Cupressus torulosa and Cedrus deodara, (4) Cedrus deodara forests on flood plain deposits, (5) Sub alpine forests of Betula utilis, (6) Alpine pastures. The author feels that conifers are ’seraI’ communities to the oak climax that have gained dominance over the area due to intense biotic factors and nature of the rock and soil.